Model Sistem Informasi Surveilans Kualitas Air Non Perpipaan (SISKA-NP) untuk Pengambilan Keputusan Program Air Bersih (Studi Kasus Pada Seksi Penyehatan Lingkungan Dinas Kesehatan Propinsi Jawa Tengah) - Riyanto, Djalal Er; Mawarni, Atik; Agushybana, Farid; Purnama, Heri (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2003)
Abstract Background : The Department of Environmental Health is one of department in Central Java Provincial Health Office. This department is responsible to water supply program. Nowdays, the department has implemented the Surveillance Information System of Nonpipe Water Supply. But till now there are some weaknesses, the data and information are used only by The Sub Department of Health Promotion and Environmental Health. There aren’t other subdepartment used the data and information, so there isn’t integration or collaboration in using some similar data or information. The objective of this research is to analyze the model of Surveillance Information System of Nonpipe Water Supply which is now implemented in The Department of Environmental Health. Methods : This is an operational research that use qualitative method and system development life cycle approach. The subjects are the chief of The Sub Department of Health Promotion and Environmental Health, the chief of the section of environmental health and also the water quality surveillance officers. While the object of this research is The Surveillance Information System of Nonpipe Water Supply which is implemented. The data will be analyzed using the content analysis, descriptive analysis and the data flow diagram . Result : After analyzed the Surveillance Information System of Nonpipe Water Supply, we found that there were some problems. The problems are rapidity, accuracy, completeness and accessibility of the data of water supply surveillance. We suggest a new system that there will be a new entity. The new entities are the provincial house of representative and the subdepartment of diseases prevention and elimination. Keywords: health information system, water quality